Shifts in literary discourse between comparison and globalisation, or the other face of cultural consciousness authority - .bala, nouari (El Omda in Linguistics and Discourse Analysis, 2025)
This research paper seeks to explore the environment in which comparative literature emerged, and to examine its connections to cultural ,social and political aspects. It also seeks to analyze the cultural exchange that took place among European societies and the emergence of the European cultural center's tendency as a translation of the center and the margin, and the impact of this on the East. Furthermore, the study aims to identify the role of pre-established models in the trajectory of literature, mainly through travel, imagery, and mirage. Additionally, it investigates the significance of literary elements cosmopolitanism –books and authors-as means of transcending linguistic boundaries and facilitating the transition to global recognition through various factors and circumstances that contribute to the widespread dissemination of literary themes and genres then explores cultural hegemony,its contexts,and its means.